Disability and Illness in Families: A Dual Burden of Caregiving and Health Challenges - Chiranjivi Acharya, (Interdisciplinary Journal of Management and Social Sciences, 2025)
Disability and illness represent intertwined human experiences. Each can serve as both a catalyst and an outcome for the other. Physical disability often results in reduced physical activity; the intensity of disability fosters despondency, while severe injury and chronic illness may evolve into enduring disability. Nevertheless, this paper endeavors to investigate the illness trajectory stemming from disability. Utilizing primary data gathered from a dozen of fully disabled members of different households by taking their interview, this study concludes that disability not only affects the individual but also instigates illness among other family members. It is not only stressful for the particular person but also becomes a stress for the family. Frequently, individuals with disabilities endure health complications, while their caregivers experience heightened levels of stress. The intersection of illness in disabled persons and stress in their caregivers underscores that disability is not merely an individual issue but a social issue, because since the impact of disability affects the entire family unit it goes out of the personal level and becomes a social issue.